Leakage sign based on contrast-enhanced CT is a predictive marker for hematoma expansion and poor prognosis in primary brainstem hemorrhage - Motohisa Koga; Yu Hasegawa; Jin Kikuchi; Aya Hashimoto; Keiichiro Furuta; Takehiro Makizono; Hidenobu Yoshitake; Kimihiko Orito; Motohiro Morioka (Brain Hemorrhages)
Objective: Although hematoma expansion is a poor prognostic factor in patients with intracerebral hemorrhage (ICH), its effect on primary brainstem hemorrhage (PBSH) remains unclear. Since we previously observed the “leakage sign” (LS) on computed tomography (CT) to be a significant predictor for hematoma expansion, we herein investigated the effect of LS in PBSH. Methods: Between January 2013 and August 2023, 515 patients with ICH were admitted to our institute. Thirty-six patients with PBSHs met the inclusion criteria, who were then divided into LS-positive (LS+) and LS-negative (LS-) groups based on the presence of LS. We evaluated hematoma expansion and prognosis at discharge. Results: Patients in the LS+ group had larger baseline hematoma volume and lower Glasgow Coma Scale scores on admission and significantly poor prognosis at discharge. Subgroup analysis revealed that LS was frequently observed within 100 min after the onset of symptoms in patients with a hematoma size of >10 mm3 on CT; additionally, patients in the LS+ group more frequently experienced hematoma expansion and had poor prognosis at discharge. Conclusions: LS is a significant predictive marker for disease severity at admission, hematoma expansion, and poor prognosis at discharge.